Analysis of Cocoa Supply Chain Risk in Kare Village, Madiun District with Method Analytic Network Process - Risqi Firdaus Setiawan; Pawana Nur Indah; Endang Yektiningsih (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
Cocoa is one of the plantation commodities whose role is quite important for the national economy of Indonesia. However, the cocoa industry faces several problems including the various risks involved in the cocoa supply chain. The aim of this study were: 1) Identifying risks in the cocoa supply chain 2) Analyzing the members of the supply chain with the highest risk 3) Evaluating and mitigating cocoa supply chain risks effectively and efficiently. An integrated analytic network process (ANP) and weighted failure mode effect analysis (WFMEA) method will be used to determine and analyze the highest risk in the cocoa supply chain. The results of the priority of the members of the value chain in the cocoa supply chain risk management are SMEs (0.43801), with the risk having the highest priority is production risk (0.29262) as well as alternative strategic priorities namely by increasing income (0.28754). The results of risk control are mainly focused on efforts to increase the income of cocoa farmers by utilizing cocoa processing byproducts such as cocoa bean pulp and cocoa pod husks. The cocoa bean pulp can be processed into nata products and cocoa juice, while the cocoa pod skin can be used as fertilizer.